Economies of Scale: The Rationale Behind the Multinationality-Performance Enigma - Stefan Eckert; Max Koppe; Eckhard Burkatzki; Simon Eichentopf; Constantin Scharf (Management International Review, 2022)
In a widely acclaimed contribution to Management International Review, Hennart (2007) challenged one of the mainstream theories of International Business, the S-curve relationship between multinationality and performance, by arguing that there is no positive impact on performance aside from the scale enhancing effect resulting from increasing multinationality. We examine his arguments by analyzing 3876 firms from Canada, Germany, Japan, the UK and the US over the period from 2002 to 2016. We find that the empirical evidence for a direct positive impact of multinationality on performance is not convincing. However, increasing multinationality leads to a significantly higher firm performance via the economies of scale-channel. Multinationality seems to be more important as a means to increase scale for firms from small home markets compared to firms from large domestic markets. Intangible assets appear to amplify the impact of scale on performance much more than the impact of multinationality on performance. In the end, it's size that matters.
Keywords: 330; Multinationality; Performance; Economies of scale; Intangible assets